Hubungan Antara Penggunaan Kontrasepsi Hormonal Dengan Kejadian Mioma Uteri di RSUD Dr.Moewardi Surakarta. - Kurniawati, Wakhidah Asri; , Yuli Kusumawati, SKM., M. Kes (Epid); , Anisa Catur Wijayanti, SKM., M.Epid (2015)
Hormonal contraceptives were estrogen and progesterone contraceptives which provide feedback to the pituitary gland through the hypothalamus, causing barriers to the follicles and ovulation. Hormonal contraception preferred by acceptors because it was more practical and effective way to prevent pregnancy. Use of hormonal contraceptives also contain risk, if exposure to estrogen and progesterone hormone is a substance triggers uterine myoma. This study aimed to test there a relationship between hormonal contraceptive use with the incidence of uterine myoma in hospitals of Dr. Moewardi Surakarta. This study was analytic observational with case control study design. The study population was all women who registered or admitted to the ward of Obstetric Gynekology in Hospital of Dr. Moewardi 2015. The case's sample are patients who diagnosed cases of uterine myoma numbered 55 people, The control's sample are the patients who did not diagnosted uterine mioma numbered 55 people in Hospital of Dr.Moewardi Surakarta. The data was collected using questionnaires, while data analysis using Chi Square. The study concluded that (1) there was an association between the use of hormonal and non-hormonal contraceptive on the incidence of uterine myoma (p=0.04, OR=2,298 95%CI: 1,147-7,473) (2) there was an association between hormonal contraceptive use and non contraception on the incidence of uterine myoma (p=0.027,0R=3,221 95%CI:1,239-8,374) (3) there was an association between the use of hormonal contraceptive pills, the incidence of uterine myoma (p=0.009, OR=7,63695%CI:1,782-32,723) (4) there was an association between hormonal contraceptive use on the incidence of injection types myoma uteri (p = 0.004, OR=11,455 95%CI:2,177-60,282) and (5 ) there was no relationship between hormonal contraceptive use on the incidence of implant types myoma uteri (p = 0.789).